(untitled) (Global Journal of Medical Research, 2022)
Carry out a literature review about the orthodontic and surgical treatments of Apert Syndrome during the different stages of growth and development Methods A search was made in the MedLine PubMed Science Direct Scopus and Wiley Online Library databases with the combination of the following terms Syndromic craniosynostosis Dental treatment orthodontic treatment Apert Syndrome surgical treatment dental care Types of the study included Systematic and literature reviews retrospective longitudinal and cohort studies series and case reviews that were published between 1990-2020 in Spanish or English articles related to other syndromes and animal or laboratory studies were excluded The articles were selected according to relevance and availability of full text repeated findings were eliminated additionally the snowball system was used in the selected articles the quality of the evidence was evaluated using the GRADE system